The implementation of chse program in courtyard hotel by marriott bali nusa dua resort in post-covid-19 pandemic - sanjaya, I Wayan Kiki; Sari, Ni Putu Sartika (Institut Pariwisata dan Bisnis Internasional, 2021)
This study is examining the implementation of CHSE program at Courtyard Hotel by Marriott Bali Nusa Dua Resort. CHSE certification program is issued by the Ministry of Tourism and Creative Economy, aimed to guarantee hygiene, health, safety and environmental sustainability for the products and services provided to tourists. This study is aimed at determining to what extend the Courtyard Hotel by Marriott Bali Nusa Dua Resort implemented CHSE protocol. This study was conducted using descriptive quantitative method with data collection techniques through observation and interviews as well as literature study. The findings were then analyzed using the theory of negotiation. The result indicated that the implementation of the CHSE protocols in training was successful. However, some improvements are still needed concerning the employee discipline, the hotel management’s readiness, and the standard operating procedure (SOP); as an attempt to convince potential tourists to visit and to stay at the hotel.